Comercialización de la papaya maradol carica papaya empacada por la empresa agrícola Jaramillo ubicada en la parroquia San Antonio del cantón Santa Rosa provincia de El Oro - Espinoza Olivares, Esther Rosario (2015)
The objective of this project is to implement a system of marketing, waxing and packing of the papaya Maradol. Therefore the research is related in design a functional model of the market for different consumers of the cantón of Santa Rosa.The viability of the project that is economically and financially based, following a methodology, conducting consumer survey, information was analyzed, with the results to determine the type of marketing the product. The application of the methodology on knowledge of concepts of the current and future state of production, marketing and packaging of the papaya Maradol, was based on the analysis of the surveys. And to the bibliographic information of related topics in order to make comparisons about marketing, and financial analysis The document is structured to determine general aspects of the content that include the introduction, objectives, information on the current state of the production, marketing, waxing and packing of papaya, Was analyzed quantitatively and qualitatively the variables of markets, production costs, working capital, variable cost, total cost, cost-effectiveness and efficiency. The investigation determined the development of marketing strategies and packaging, as determined by the supply and demand, and the possible competition in the middle. Which allowed the projection of the supply and demand for the next 5 years of the product. So that your marketing will expand to other market provincial and because it's not international markets on the basis of the comparative advantages of production and marketing of the product. Meeting the demands of quality determining factor to ensure other markets.Furthermore, he made a Technical Analysis, where we observed the growth or projection of the company and established the location and the most suitable environment. Finally, the research determined that the project of Marketing, Waxing and Packing of the papaya Maradol is cost-effective.